Healthcare and biomedical technology in the 21st Century : an introduction for non-science majors - Kiani, Mohammad F.; Samuel, Solomon Praveen (Springer, 2014)
This textbook introduces students not pursuing degrees in science or engineering to the remarkable new applications of technology now available to physicians and their patients and discusses how these technologies are evolving to permit new treatments and procedures. The book also elucidates the societal and ethical impacts of advances in medical technology, such as extending life and end of life decisions, the role of genetic testing, confidentiality, costs of health care delivery, scrutiny of scientific claims, and provides background on the engineering approach in healthcare and the scientific method as a guiding principle. This concise, highly relevant text enables faculty to offer a substantive course for students from non-scientific backgrounds that will empower them to make more informed decisions about their healthcare by significantly enhancing their understanding of these technological advancements.